Gene Expression Underlying Teloblast Formation in Leech (Annelida: Hirudinae) - Hsiao, Samuel; Saglam, Naim; Saunders, Ralph; Shain, Daniel H. (Sage Publications Ltd, 2026)
Objective: Species of glossiphoniid leech provide model systems for exploring fundamental questions in evolutionary and developmental biology. In this study, we took advantage of large embryonic cells and stereotypical cleavage patterns in the leech, Helobdella austinensis, to identify genes associated with the births of teloblasts and their lineage specifications.Methods: Using staged embryos and pools of dissected precursor cells and teloblasts, a systematic computational comparison of staged and cell type-specific transcriptomic data was employed to identify unique gene sets associated with mesodermal (M), neuroectodermal (N) and teloblast (M + N) cell formation.Results and Conclusions: Our predicted candidate genes comprised sets of nucleic acid binding factors as anticipated but displayed little similarity with differentiation factors in other metazoans (eg, mammals, cnidarians), suggesting that stem cell/lineage induction processes have diverged across the Animalia and may reflect fundamentally different modes of embryonic development.
Keywords: stem cell; lineage; transcriptome; RNAseq; glossiphoniid; development; Lophotrochozoa